MASS PRODUCTION AND RECOVERY OF L- LYSINE BY MICROBIAL FERMENTATION USING BREVIBACTERIUM FLAVUM - S. Irshad; M. Faisal; A. S. Hashmi; M. M. Javed; M. E. Baber; A. R. Awan; A. A. Anjum (Journal of Animal and Plant Sciences, 2015)
A simple and cheap method of lysine production was developed which can be exploited on commercial scale to save foreign exchange. In present study lysine was produced at mass scale in 10 litre flask with 5 litre fermentation medium having pre-treated molasses (15 brix) as substrate by Brevibacterium flavum. Lysine content in fermented broth was 2.0167 percent. It was recovered from broth by passing through ion exchange resin column, using elution buffer (tris-HCl, pH 9). Crude brown crystals of lysine (40gm/500mL) were concentrated by evaporation (80˚C) of fermented broth and recovered with 95% ethanol at 4oC. It was decolourized with 0.5% activated charcoal, pale yellow pure crystals of Lysine (25 gm) were obtained with 95% ethanol. High concentration of lysine in the form of crystals was produced with 62.5 percent purity and concentrated fermented broth having 8% lysine can be safely used in poultry rations as a source of Lysine. It was concluded that microbial production of lysine by fermentation is a cheap and valuable method than others being used in industry.
Keywords: Lysine; Brevibacterium flavum; feed industry; ion exchange resin; fermentation